Sensitivity and Specificity of Ultrasonographic Compared with CT Angiography in Detecting Femoropopliteal and Infrapopliteal Arterial Lesions in Lower Extremity Arterial Disease in Dr. Mohammad Hoesin General Hospital Palembang - Radi Noorsyawal; Kemas Dahlan; Hanna Marsinta; Irfannuddin (Sriwijaya Journal of Surgery, 2021)
Background: Peripheral artery disease (PAD) is a chronic occlusive arterial disease of the extremities caused by atherosclerosis.1 It is estimated that 20-30% of the population worldwide suffered PAD.2 PAD is associated with a 1-year mortality and limb loss rate of 20%.7 Critical limb ischemia (CLI) is a late stage clinical presentation of PAD. Imaging of the entire artery is possible using CT angiography. However, CT angiography has its drawbacks because the contrast used can be nephrotoxic, the risk of allergies, expensive, and not all health services have it. Ultrasonographic’s (USG) sensitivity, specificity and accuracy were 96.55%, 61.53%, and 78.84% for detecting lower limb distal artery lesions.11 Ultrasonographic does not require the use of contrast, radiation, low cost and almost all health services have them.12 However, the Ultrasonographic examination has its limitations depending on the operator's capabilities. It is therefore necessary to conduct research that have never been previously studied in South Sumatra. Methods: This study is a diagnostic test study that examines the sensitivity and specificity of ultrasound in detecting LEAD artery lesions. The samples were 29 patients. Results: At the femoropopliteal level, the results obtained were 91% sensitivity and 86% specificity. At the infrapopliteal level, the results obtained were 95% sensitivity and 87% specificity. Conclusion: Ultrasonographic has high sensitivity and specificity in detecting LEAD’s lesions